2007
DOI: 10.1097/wad.0b013e3181461740
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion About Alzheimer Disease Among Blacks, Hispanics, and Whites

Abstract: Recent research has documented notable differences in knowledge, awareness, and cultural beliefs about Alzheimer disease (AD) among groups defined by race and ethnicity. The present study was conducted to assess racial differences in knowledge and attitudes about AD among a national sample of adults. Data from 1,176 adults aged 35 years and over (48.6% White, 25.7% Black, and 25.8% Hispanic) obtained via telephone interview were used in this study. Although some notable group differences defined by race/ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 45 publications
9
112
2
Order By: Relevance
“…', which has to be answered on a four-or five-point Likert scale; variations in response typically range from 'very concerned' to 'not at all concerned'. Among three USAmerican surveys (Alzheimer's Association 2003; Alzheimer's Association and American Heart Association 2008; Connell et al 2007), the percentage of respondents categorised as concerned about developing Alzheimer's disease (AD) ranged from 26 to 49 %. In a random sample of Australians (N = 2000), 48 % of participants said that they were at least a little worried about developing dementia (Low and Anstey 2009).…”
Section: Prevalence Of Dw In the General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…', which has to be answered on a four-or five-point Likert scale; variations in response typically range from 'very concerned' to 'not at all concerned'. Among three USAmerican surveys (Alzheimer's Association 2003; Alzheimer's Association and American Heart Association 2008; Connell et al 2007), the percentage of respondents categorised as concerned about developing Alzheimer's disease (AD) ranged from 26 to 49 %. In a random sample of Australians (N = 2000), 48 % of participants said that they were at least a little worried about developing dementia (Low and Anstey 2009).…”
Section: Prevalence Of Dw In the General Populationmentioning
confidence: 99%
“…general practitioner), as they perceived there was little that could be done (Corner and Bond 2004). Less than one quarter of respondents reported believing they were 'well prepared' to handle a family member's AD diagnosis (Connell et al 2007). A lack of coping resources may also be indicated by the finding that even though a large majority of Americans think that it is at least somewhat important to plan for AD, 82 % have not made plans for the possibility of getting AD (MetLife Foundation 2011).…”
Section: Lack Of Coping Strategiesmentioning
confidence: 99%
“…Blacks and Hispanics were more likely to view cognitive decline and AD as a normal experience of aging and also were more optimistic about the prospects of future developments in AD treatments. Another difference was the preparedness for handling a diagnosis: Hispanic participants reported feeling equipped to navigate diagnostic disclosure situations, whereas blacks and whites did not (Connell et al, 2007).…”
Section: Cultural Differencesmentioning
confidence: 99%
“…Connell, Scott Roberts, and McLaughlin (2007) conducted a national study of white, black, and Hispanic public opinions about AD and treatment. Blacks and Hispanics were more likely to view cognitive decline and AD as a normal experience of aging and also were more optimistic about the prospects of future developments in AD treatments.…”
Section: Cultural Differencesmentioning
confidence: 99%
“…AD Worry is a relatively unexplored phenomenon but widespread within the general population, at least in Western societies. Estimates of its community prevalence have ranged from 26% to 76.6% [11][12][13][14][15][16]. Cultural differences in the presence of AD Worry were reported in a few studies, worries about AD were found to be mostly common in Western cultures [9].…”
Section: Introductionmentioning
confidence: 99%